DOES EMPIRICAL VITAMIN D REPLACEMENT IMPROVE LFTS IN PATIENT WITH NAFLED AND TYPE-II DM (The Research of Medical Science Review, 2025)
Objective: To observe the effects of vitamin D replacement in improving LFTs in patients with NAFLD and Type-II DM Study Design: A single blind, prospective randomized trials Study Duration: 06 months Study Place: Divisional Head Quarter Hospital Mirpur Azad Kashmir Methods: Total 136 individuals were included in study, among them 86 were males and 50 were females. 02 groups were made with equal distribution of participants. Group A was given oral vitamin D tablet 20,000IU every week for 24 weeks and Group B was given placebo. LFTS, serum IGF and HBA1C was done before and after the oral vitamin D to look for the trend in improvement. Results: Both group A and B were observed for 06 months, and pre vitamin D LFTs and HBA1c and IGF levels were done. The group A showed improving trend in ALT and AST following vitamin D therapy and serum IGF showed modest improvement. HBA1C also showed improvement in trend. Conclusion: From our study, we can conclude that oral vitamin D therapy has beneficial effects in improving the liver function tests and glycaemic tolerance in patients with NAFLD and type II diabetes mellitus.